Orquestra UFGD: processos educativos emergentes em com-vivência musical - Costa, Thais Fernandes (2021)
The UFGD Orchestra is a project developed by the Dean of Extension and Culture of the Federal University of Grande Dourados (UFGD) and started its activities in 2013. Currently, the group has approximately 45 participants, including children, youth and adults from Dourados and region who rehearse twice a week, at night. The UFGD Orchestra is characterized as a community orchestra that is constituted as an not usual instrumental formation, welcoming people of different technical and musical levels in different instruments, not being restricted to a symphonic formation. The main objective of this investigation was to unveil the educational processes emerging from the social practice of making music in conjunction with musicians who have been participating or have participated in the university extension project “Orquestra UFGD” for at least four years. At first, we performed a bibliographic search and started data collection, using a questionnaire on Google Form with open and closed questions as an instrument. We counted on the collaboration of 75 people and the the questionnaire helped us to create the criteria to select the interviewees. In total, we conducted 8 interviews and chose to use the semi-structured interview procedure. To collect and analyze the data, we chose to carry out qualitative research with a phenomenological approach in which, after the transcription of the interviews, we carried out the ideographic analysis to find the units of meaning and to construct which categories emerged from the analysis for the elaboration of the nomothetic matrix where we arrived at the following categories: A) “Time-space for personal-social transformation into a musical experience:“ We get out of our world ”; B) Tensions and relaxations in musical experience: “Then you leave there with another head, do you understand? With another thought ”; C) Learning how to better play an instrument in musical experience: “Many things I didnt know, I learned there, at the time of practices, including with colleagues”. In the analysis, we highlight the educational processes reported of learning in musical coexistence, understanding that these processes are related to the senses and personal or collective experiences as being awareness of the world through making music with the Orquestra UFGD group.